Compassionate Use of Tocilizumab for Treatment of SARS-CoV-2 Pneumonia. (23rd June 2020) - Jordan, Stanley C; Zakowski, Phillip; Tran, Hai P; Smith, Ethan A; Gaultier, Cyril; Marks, Gregory; Zabner, Rachel; Lowenstein, Hayden; Oft, Jillian; Bluen, Benjamin; Le, Catherine; Shane, Rita; et al.
Abstract: Background: Preliminary data from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia patients indicate that a cytokine storm may increase morbidity and mortality. Tocilizumab (anti-IL-6R) is approved by the Food and Drug Administration for treatment of cytokine storm associated with chimeric antigen receptor T-cell therapy. Here we examined compassionate use of tocilizumab in patients with SARS-CoV-2 pneumonia. Methods: We report on a single-center study of tocilizumab in hospitalized patients with SARS-CoV-2 pneumonia. All patients had confirmed SARS-CoV-2 pneumonia and oxygen saturations <90% on oxygen support with most intubated. We examined clinical and laboratory parameters including oxygen and vasopressor requirements, cytokine profiles, and C-reactive protein (CRP) levels pre- and post-tocilizumab treatment. Results: Twenty-seven SARS-CoV-2 pneumonia patients received one 400 mg dose of tocilizumab. Interleukin (IL)-6 was the predominant cytokine detected at tocilizumab treatment. Significant reductions in temperature and CRP were seen post-tocilizumab. However, 4 patients did not show rapid CRP declines, of whom 3 had poorer outcomes. Oxygen and vasopressor requirements diminished over the first week post-tocilizumab. Twenty-two patients required mechanical ventilation; at last follow-up, 16 were extubated. Adverse events and serious adverse events were minimal, but 2 deaths (7.4%) occurred that were felt unrelated to tocilizumab. Conclusions: Compared to published reports on the morbidity and mortality associated with SARS-CoV-2, tocilizumab appears to offer benefits in reducing inflammation, oxygen requirements, vasopressor support, and mortality. The rationale for tocilizumab treatment is supported by detection of IL-6 in pathogenic levels in all patients. Additional doses of tocilizumab may be needed for those showing slow declines in CRP. Proof of efficacy awaits randomized, placebo-controlled clinical trials. Abstract : We found that a single dose of tocilizumab 400 mg given intravenously for compassionate use in 27 patients with severe SARS-CoV-2 pneumonia appeared to offer benefits in reducing inflammation, oxygen requirements, vasopressor support, and mortality.